Photoresist composition and photoetching patterning application
By using a multi-component elastomer photoresist composition, a crosslinking network is constructed using polyene functionalized precursor, thiol crosslinking agent and bifuran crosslinking agent, the resolution in the existing photoresist technology is solved. , line width roughness, pattern rigidity, reaction mechanism limitations and environmental impact issues, achieving efficient and environmentally friendly micro-nano pattern formation.
Patent Information
- Application Number
- CN202411820715.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing photoresist technology has problems with resolution and line width roughness. The high flexibility of sulfide bonds in thiol-ene photoresist leads to insufficient pattern rigidity, the limitations of the reaction mechanism leads to limited processing efficiency and application range, and light The additives are complex during the synthesis of resist compositions and may have negative environmental impacts.
Using multi-component elastomer photoresist compositions, including polyene functionalized precursors, thiol crosslinking agents and bisfuran crosslinking agents, the crosslinking network is constructed through ultraviolet light and high temperature to initiate chemical reactions, so as to achieve exposure zones and Solubility differences in non-exposed areas and the introduction of reversible dynamic covalent bonds for easy material removal and cleaning.
The photoresist with high elastic modulus and high molding ability is achieved, forming a micro-nano pattern with low defects, high contrast and high intensity, reducing the exposure dose of the photoresist, improving flexibility, and reducing the impact on the environment. Suitable for a variety of lithography technologies.
Smart Images

Figure CN119439621A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photolithography materials, and in particular relates to a class of polymer compositions and photolithography patterning applications. Background Art
[0002] Photolithography is a patterning process that forms the desired shape of micrometer / nanometer size by irradiating photosensitive or electron-sensitive materials with ultraviolet light or exposing them to electron / ion beams. As a key material in micro-nano processing technology, polymer photoresist plays an important role in integrated circuit chip manufacturing, fine pattern circuit processing and other fields. In recent years, as integrated circuits continue to develop towards smaller sizes, the performance requirements for photoresists are also getting higher and higher.
[0003] Traditional chemically amplified photoresists mainly contain photoacid generators (PAGs). During the exposure process, photons are absorbed by PAGs and then release acids. The acids act as catalysts during the post-baking process to remove the protective groups of the resin, making the resin easy to dissolve. This process forms a chain reaction, and one photoacid catalyzes multiple reaction sites, achieving an "amplification" effect and improving the reaction efficiency. However, the diffusion of PAGs in the polymer will seriously affect the resolution and line width roughness of the photoresist, and the unevenness of the photoresist film caused by PAG aggregation and separation will cause image blurring and other problems. In order to solve these above-mentioned problems, highly sensitive and highly selective thiol-ene click crosslinking is widely used in the field of photoresists. Thiol-ene click chemistry is a powerful and widely used tool in materials chemistry. As an alternative resin that forms a structurally homogeneous network through a step-growth free radical process, this type of photoresist is mainly composed of a prepolymer and a crosslinker, and the difference between the exposed area and the non-exposed area is achieved through photocrosslinking of thiol groups and double bonds. Under ultraviolet or extreme ultraviolet light, it decomposes to generate free radicals, which capture a hydrogen atom from the thio compound to generate a thiol radical. The thiol radical attacks the allyl unit to generate a carbon radical, which in turn captures a hydrogen atom from the thio compound to generate a thiol radical. This process continues until a coupling reaction of two free radicals occurs. However, the thioether bond is highly flexible, and the pattern after development is not rigid enough. In order to improve the mechanical strength of the material, a rigid structure is introduced to achieve this. Currently, the main thiol-ene photoresist research focuses on organic-inorganic hybrid systems. However, thiol-ene click photoresists based on pure polymers can theoretically give photoresists multifunctionality, such as introducing polymer elastomer lithography, which has high potential application prospects in micro-nano sensing and flexible stretching.
[0004] In summary, the existing technology has the following problems that need to be solved: first, the resolution and line width roughness of traditional chemically amplified photoresists; second, the problem of insufficient pattern rigidity caused by the excessive flexibility of thioether bonds in thiol-ene photoresists; third, the limited processing efficiency and scope of application caused by the limitations of the reaction mechanism; fourth, the problem that the additives in the synthesis process of photoresist compositions are complex and may have a negative impact on the environment. The existence of these problems not only restricts the development of photoresist technology, but also limits its application in a wider range of fields. Summary of the invention
[0005] The present invention provides a multi-component elastomeric photoresist composition with high elastic modulus and high molding ability and a method for forming a photolithographic pattern using the same. The elastomeric photoresist is composed of three components: a polyene functionalized precursor, a thiol crosslinking agent and a bifuran crosslinking agent. The polymer photoresist can construct a crosslinking network by initiating a chemical reaction between different components through ultraviolet light and high temperature, thereby achieving a solubility difference between an exposed area and a non-exposed area, thereby obtaining a micro-nano pattern with low defects, high contrast and high strength during development. At the same time, the introduction of reversible dynamic covalent bonds (DA and rD-A) in the elastomeric photoresist system can achieve dissociation after secondary heating, which is beneficial to material removal and cleaning after photolithography. The present invention further relates to a method for forming a photolithographic pattern using the photoresist composition and the use of the photoresist composition.
[0006] The present invention discloses a photoresist composition, which comprises compounds of formula I, formula II and formula III:
[0007]
[0008] In the compound described in formula I:
[0009] X is selected from one of olefins; more preferably X is maleimide;
[0010] R1 is one of the flexible oligomers; R1 is more preferably one of the following structural formulas:
[0011]
[0012] Wherein: n is selected from an integer between 1 and 30. n is more preferably an integer between 10 and 15;
[0013]
[0014] In the compound described in formula II:
[0015] R2 is selected from one of alkyl, thiol propionate, thiol acetate and aromatic, more preferably thiol propionate;
[0016] m is selected from an integer between 2 and 8; more preferably 3, 4 or 6;
[0017]
[0018] In the compound described in formula III:
[0019] R3 is selected from one of alkanes, ketones, benzene and ethers; more preferably one of methane, propane, ketone, benzene and thioether.
[0020] For the technical scheme described above, it is further preferred that the precursor compound of formula I, its hard segment mainly includes the end-capping agents norbornene carboxylic acid and norbornene anhydride, and the soft segment is selected from polyethylene glycol, polytetramethylene ether glycol, polycaprolactone diol; the molecular weight range is 100-5000g / mol, and the more preferred molecular weight range is 500-2000g / mol; the hard segment also includes a side-chain grafted maleimide monomer.
[0021] For the technical scheme described above, it is further preferred that the weight ratio of the compounds of formula I, formula II and formula III is (5-9): (0.5-2.5): (0.5-2.5); preferably, the weight ratio of the compounds of formula I, formula II and formula III is (6-8): (1-2): (1-2); the most preferred weight ratio is 8:1:1.
[0022] For the technical solution described above, it is further preferred that the photoresist composition also includes an organic solvent; more preferably, the organic solvent is selected from at least one of toluene, xylene, n-hexane, dichloromethane, chloroform, ethyl acetate, and PGMEA (propylene glycol methyl ether acetate); the most preferred solvent is propylene glycol methyl ether acetate.
[0023] Another aspect of the present invention is to utilize the photoresist composition described above for photolithographic patterning application, spin-coat the photoresist composition described above on a silicon wafer or quartz wafer substrate, and dry to form a photoresist film; expose the photoresist film to deep ultraviolet, extreme ultraviolet or electron beam radiation for exposure; and bake at a low temperature after exposure: and develop with a developer to obtain a photolithographic pattern.
[0024] For the technical solution described above, it is further preferred that the developer is selected from at least one or more mixtures of isopropyl alcohol, ethyl acetate, 2-heptanone, 4-methyl-2-pentanone and cyclohexanone.
[0025] For the technical solution described above, it is further preferred that the method also includes high-temperature baking of the patterned silicon wafer, and the finished product for optical cross-linking is transferred to a higher temperature; to initiate the Diels-Alder cyclization reaction of furan and side chain maleimide; and finally developing with a developer.
[0026] For the technical solution described above, it is further preferred that the temperature of the low-temperature baking is 70° C. and the time is 60 seconds.
[0027] For the technical solution described above, it is further preferred that post-baking is performed after development to promote the cross-linking reaction; preferably, the post-baking temperature is 80° C. and the time is 60 seconds.
[0028] For the technical solution described above, it is further preferred that the high temperature baking temperature is 130° C. and the time is 30 minutes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. Efficient participation of multiple functional groups: The three active functional groups of thiol, end-capped olefin and side-chain olefin in the composition all actively participate in the subsequent reaction, ensuring the high efficiency and comprehensiveness of the reaction.
[0031] 2. Rapid photocrosslinking construction: During the material exposure stage, the precursors, thiol and difuran monomer components are in a "latent" state. Once the photoresist is exposed to ultraviolet light or electron beams, the thiol molecules quickly disintegrate, and the unstable thiol radicals generated can quickly propagate to the strained norbornene bonds, forming stable thioether bonds through a series of reactions, thereby completing the construction of the photocrosslinking network in a short time, and the system molecular weight increases rapidly.
[0032] 3. High efficiency of thiol-ene reaction: The rate of thiol-ene reaction is highly dependent on the chemical structure of olefins. Among them, norbornene with high electron content and strong strain capacity shows the highest reaction efficiency, which further improves the cross-linking speed and performance of photoresist.
[0033] 4. Orthogonal reaction mechanism ensures difference: The light-induced thiol-ene click reaction and the thermally initiated Diels-Alder (DA) cyclization reaction are independent of each other and do not interfere with each other. This orthogonal reaction mechanism ensures significant differences in molecular weight and cross-linking degree between the exposed and non-exposed areas, providing a basis for subsequent development and pattern formation.
[0034] 5. Clear molecular structure and simple synthesis: The photoresist composition provided by the present invention has a clear molecular structure and does not require the addition of additional ingredients such as photoacid generators, surfactants, viscosity enhancers and quenchers. Compared with nanoparticles or polymer photoresists, the composition of the present invention belongs to the molecular field, has a simple and clear structure, and the synthesis process is simple and easy with high repeatability.
[0035] 6. Suitable for model photoresist research: Due to its clear molecular structure and simple synthesis process, the composition of the present invention is very suitable as a model photoresist for studying advanced exposure mechanisms and photolithography technology, providing strong support for the further development of photolithography technology.
[0036] 7. High-resolution micro-nano patterns: After the exposure and development process, the exposed area has a large molecular weight and a high degree of crosslinking, while the non-exposed area has a small molecular weight and a low degree of crosslinking. This difference enables the formation of micro-nano negative lines and patterns after development in a solvent, meeting the needs of high-precision lithography technology.
[0037] 8. Environmental friendliness and sustainability: The use of simple molecular structures and additive-free photoresist compositions helps reduce the impact on the environment and improve sustainability. This is in line with the current development trend of green chemistry and environmental protection technology.
[0038] 9. Wide application prospects: The photoresist composition provided by the present invention is applicable to a variety of photolithography techniques, including 254nm ultraviolet lithography, 365nm ultraviolet lithography, deep ultraviolet lithography, extreme ultraviolet lithography or electron beam lithography, etc. The sensitivity of the highly sensitive photoresist composition can reach 20mJ / cm 2 ~200mJ / cm 2 .
[0039] Its excellent performance and broad application prospects make the present invention have great potential in the fields of semiconductor manufacturing, micro-nano processing, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a photolithography process flow provided in an embodiment of the present invention.
[0041] Figure 2 This is a physical picture of the coating in Example 1 of the present invention; the figure shows a physical picture of the photoresist composition spin-coated on a silicon wafer, proving that it has good film-forming ability and adhesion ability.
[0042] Figure 3 This is the infrared spectrum of the precursor in Example 1 of the present invention; the figure shows that 1640cm -1 (C=C stretching vibration) and 814cm -1 The precursor has traces of olefins at 1730 cm -1 1400cm -1 and 1190cm -1 Three new absorption bands appeared, which were attributed to C=O stretching vibration, CN stretching vibration and COC stretching vibration, respectively. It proved that norbornene successfully capped polyethylene glycol and successfully grafted maleimide on the side chain.
[0043] Figure 4 This is the elastic modulus mapping of the photolithography pattern in Example 1 of the present invention. The modulus distribution is uniform, the average elastic modulus is 1.437 GPa, and the scale is 400 nm.
[0044] Figure 5This is an optical microscope picture of the coating film of Example 1 of the present invention, which has no crystals and no insoluble matter, proving its good film-forming property and solubility.
[0045] Figure 6 This is a 5 μm line pattern obtained by Example 1 of the present invention using a 365 nm exposure machine. The pattern is clean and the lines are defect-free.
[0046] Figure 7 : is the adhesion curve between the film and the silicon wafer in Example 1 of the present invention. The maximum adhesion is attributed to the interaction between the molecules and the hydroxyl groups on the surface of the silicon wafer.
[0047] Figure 8 A thermal analysis curve is provided for Example 1 of the present invention; the figure shows that a glass transition temperature occurs at 13.4°C, proving that cross-linking and curing has been carried out.
[0048] Fig. 9 This is a thermogravimetric analysis diagram of the precursor in Example 1 of the present invention; the diagram shows that the pyrolysis temperature exceeds 300°C, proving that it has good thermal stability.
[0049] Fig.10 The film morphology and thickness measurement diagram of the photoresist film prepared in Example 1 of the present invention under AFM; the figure shows that the film roughness of the photoresist composition is 0.631nm, proving that a smooth film is formed.
[0050] Fig.11 This is the X-ray diffraction spectrum of Example 1 of the present invention; the figure shows that the photoresist composition has a typical amorphous polymer broad peak at 2θ=20°, proving that it presents an amorphous structure.
[0051] Fig.12 The photoresist film in Example 2 of the present invention is patterned under 254 nm exposure using an optical microscope, and a feature size of 25 μm is patterned using a custom-made mask.
[0052] Fig.13 It is the infrared spectrum of the precursor in Example 3 of the present invention; its characteristic functional groups are consistent with those in Example 1, but due to the increase in the main chain molecular weight, the transmittance of its functional groups decreases.
[0053] Fig.14 This is the elastic modulus mapping of the photolithography pattern in Example 3 of the present invention. The modulus distribution is uniform, the average elastic modulus is 1.054 GPa, and the scale is 400 nm.
[0054] Fig.15 The adhesion curve of the film and the silicon wafer in Example 3 of the present invention shows that the adhesion is attributed to the interaction between the molecules and the hydroxyl groups on the surface of the silicon wafer.
[0055] Fig.16This is a 5 μm line pattern obtained by Example 3 of the present invention using a 365 nm exposure machine. The pattern is clean but has a low contrast.
[0056] Fig.17 The film morphology and thickness measurement diagram of the photoresist film prepared in Example 3 of the present invention under AFM; the figure shows that the film roughness of the photoresist composition is 0.515nm, proving that a smooth film is formed.
[0057] Fig.18 This is the pattern obtained by Example 4 of the present invention under a 254nm light source. The pattern is clear and the lines are defect-free.
[0058] Fig.19 This is the pattern obtained by Example 5 of the present invention under a 254nm light source. The pattern is clear but has obvious defects.
[0059] Fig. 20 The adhesion curve of the film and the silicon wafer in Example 5 of the present invention shows that the adhesion is attributed to the interaction between the molecules and the hydroxyl groups on the surface of the silicon wafer.
[0060] Fig.21 The film morphology and thickness measurement diagram of the photoresist film prepared in Example 5 of the present invention under AFM; the figure shows that the film roughness of the photoresist composition is 1.75nm, and its roughness becomes larger.
[0061] Fig. 22 This is the pattern obtained by Example 6 of the present invention under a 254nm light source. The pattern is clear and the lines are defect-free.
[0062] Fig.23 The film morphology and thickness measurement diagram of the photoresist film prepared in Example 6 of the present invention under AFM; the figure shows that the film roughness of the photoresist composition is 1.96nm, and its roughness becomes larger.
[0063] Fig.24 This is an optical microscope image of the coating film of Example 7 of the present invention, which shows the presence of insoluble matter and poor solubility.
[0064] Fig.25 This is an optical microscope picture of the coating film of Example 8 of the present invention, which contains insoluble matter and crystals, and has poor film-forming property and solubility.
[0065] Fig.26 This is the elastic modulus mapping of the photolithography pattern in Example 9 of the present invention. The modulus distribution is uniform, the average elastic modulus is 1.257 GPa, and the scale is 400 nm.
[0066] Fig. 27 This is the elastic modulus mapping of the photolithography pattern in Example 10 of the present invention. The modulus distribution is uniform, the average elastic modulus is 1.028 GPa, and the scale is 400 nm.
[0067] Fig.28 The optical microscope image in Example 11 of the present invention has a feature size of 25 μm.
[0068] Fig.29 The optical microscope image in Example 12 of the present invention has a feature size of 25 μm.
[0069] Fig.30 Ultra-high resolution AFM image of electron beam lithography in Example 13 of the present invention, showing that the line feature size is 122nm, proving its high-resolution patterning capability
[0070] Fig.31 This is the patterned EDS mapping (COS) of Example 2 of the present invention; the figure shows that the photoresist composition contains C, O, and S elements after patterning, and the element distribution shows that the pattern is uniform and the unexposed area has been completely removed.
[0071] Fig.32 From the patterned optical microscope comparison images of Comparative Example 1 and Example 1, it can be clearly seen that the pattern of Comparative Example 1 is shallower and thinner due to the absence of rigid structures such as furan, proving that the flexible system cannot support thicker films. On the contrary, the pattern of Example 1 is clearer.
[0072] Fig.33 This is the elastic modulus mapping of the photolithography pattern of comparative example 1, the modulus distribution is uniform, the average elastic modulus is 82.955 MPa, and the scale bar is 400 nm.
[0073] Fig.34 The adhesion curve of the film and the silicon wafer in Comparative Example 2 shows that the maximum adhesion is only 7.83 nN, which is much lower than that of Example 1 of the present invention.
[0074] Fig.35 Optical microscope image of water development in Comparative Example 3. DETAILED DESCRIPTION
[0075] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in more different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0077] The following are specific embodiments, which are intended to further explain the present invention in detail to help the technical personnel and researchers in the field to further understand the present invention. The relevant technical conditions do not constitute any limitation to the present invention. Any form of modification made within the scope of the claims of the present invention is within the scope of protection of the claims of the present invention.
[0078] Except as indicated in the operating examples, or where otherwise indicated, all numbers expressing quantities of ingredients, physicochemical properties, and so forth used in the specification and claims are to be understood as being modified in all instances by the term "about".
[0079] The embodiment of the present application provides a photoresist composition, which is composed of a tetraene polymer precursor, a thiol crosslinker and a bisfuran crosslinker. It includes a precursor compound of formula I, wherein the hard segment mainly includes end-capping agents norbornene carboxylic acid and norbornene anhydride, and the soft segment is selected from polyethylene glycol, polytetramethylene ether glycol, and polycaprolactone glycol; the molecular weight range is 100-5000 g / mol, and the more preferred molecular weight range is 500-2000 g / mol. The hard segment also includes a maleimide monomer grafted with a side chain.
[0080] In the embodiment of the present application, the photoreactive group is selected from carbon-carbon double bonds and thiol groups, and the thermal excitability group is selected from maleimide and carbon-carbon double bonds. These active functional groups can efficiently participate in subsequent reactions after exposure, ensuring the efficiency and comprehensiveness of the reaction. In the material exposure stage, the precursor, thiol and difuran monomer components are in a "latent" state. Once the photoresist is exposed to ultraviolet light or an electron beam, the thiol molecules disintegrate rapidly, and the unstable thiol radicals generated can quickly propagate to the strained norbornene bonds, forming stable thioether bonds through a series of reactions, thereby completing the construction of the photocrosslinked network in a short time, and the system molecular weight increases rapidly.
[0081] This orthogonal reaction mechanism ensures that the exposure area and the non-exposure area have significant differences in molecular weight and crosslinking degree, resulting in differences in the solubility of the exposed and non-exposed parts of the photoresist in organic solvents, so that a pattern of a desired shape can be obtained after development. Compared with the traditional polymer photoresist system, the photoresist composition provided by the embodiment of the present invention reduces the photoresist exposure dose and improves the photoresist flexibility. The introduction of rigid molecules solves the problem that the metal oxide core in the metal oxide nanoparticles modified by organic groups has a high light absorption rate, and reduces the defect rate of the photolithography lines.
[0082] The present application provides a photoresist composition, comprising: a tetraene polymer precursor, a thiol crosslinking agent, a bisfuran crosslinking agent and a solvent. The tetraene polymer precursor described in the present application is generally formulated as PEGnNB-MI, wherein n is the relative molecular weight of polyethylene glycol. The soft segment of the polymer of formula I is selected from polyethylene glycol, polytetramethylene ether glycol, polycaprolactone glycol, and has a molecular weight range of 100-5000 g / mol; a more preferred molecular weight range is 500-2000 g / mol; the hard segment includes the end-capping agent norbornene carboxylic acid and norbornene anhydride.
[0083] In the embodiment of the present application, the difuran crosslinker is 2,2'-(propane-2,2-diyl)difuran, di(furan-2-ylmethyl)sulfide, 2,2'-(oxybis(methylene)difuran, 1,2-di(furan-2-yl)ethane-1,2-dione. In the embodiment of the present application, the photoresist composition described in Formula II, the multifunctional thiol, includes dipentaerythritol hexa(3-mercaptopropionate), pentaerythritol tetra(mercaptopropionic acid) ester, pentaerythritol tetra(thioglycolic acid) ester, trimethylolpropane tris(thioglycolic acid), trimethylolpropane tris(mercaptopropionic acid).
[0084] The photoresist was exposed using the composition ratio and exposure method in the following embodiment, and the photoresist solution was coated on the surface of the silicon wafer and pre-baked at 80° C. for 60 seconds. The detection was performed according to the following steps:
[0085] (1) A solution consisting of a photoresist composition and a solvent was spin-coated on each silicon wafer, and the film thickness after drying was 0.05 μm.
[0086] (2) Expose to line or gap patterns in different exposure modes while gradually changing the exposure amount.
[0087] (3) Immerse the silicon wafer in developer and observe the patterns on the silicon substrate using a microscope.
[0088] The line width resolution of 1μm is the effective resolution. The minimum exposure dose of the photoresist at the effective resolution is measured, that is, the sensitivity.
[0089] Example 1
[0090] Preparation method of tetraene polymer precursor:
[0091]
[0092] 1. Accurately weigh each component: Polyethylene glycol: Mn = 600 g·mol -1 , 0.12g;
[0093] Norbornene anhydride: 1.64 g;
[0094] N-Carbamoylmaleimide: 0.224 g;
[0095] 2. Polyethylene glycol, norbornene anhydride and catalyst were dissolved in an organic solvent and reacted at 60°C overnight.
[0096] 3. The product of 2 and the catalyst were dissolved in DMF and activated in the dark for 2 hours.
[0097] 4. Maleimide is then added to the reaction.
[0098] 5. The crude product is purified by recrystallization.
[0099] Preparation method of photoresist composition:
[0100] 1. Accurately weigh each component:
[0101] Tetraene polymer precursor: PEG 600 NB-MI, wherein n represents the relative molecular weight of polyethylene glycol, specifically in the range of 1000 g / mol, and accounts for 80 wt% of the total weight.
[0102] Thiol cross-linking agent: dipentaerythritol hexa(3-mercaptopropionic acid) ester, accounting for 10 wt % of the total weight.
[0103] Bisfuran crosslinking agent: 2,2'-(propane-2,2-diyl)difuran, accounting for 10 wt% of the total weight.
[0104] 2. Evenly mix the tetraene polymer precursor, the thiol crosslinking agent and the difuran crosslinking agent to obtain a mixture.
[0105] 3. Add the above mixture to propylene glycol methyl ether acetate (PGMEA) solvent at a concentration of 50 mg / mL and continue stirring until completely dissolved.
[0106] 4. Filter the mixture using a 0.22 μm filter membrane to remove impurities.
[0107] Methods for forming thin film patterns, such as Figure 1 :
[0108] 1. Coating: Spin-coat the photoresist composition prepared above on a silicon wafer with a coating thickness of 0.05 μm.
[0109] 2. Pre-bake: Pre-bake at 70°C for 60 seconds to remove the solvent.
[0110] 3. Exposure: Use deep ultraviolet lithography machine for exposure, the exposure dose is 25mJ / cm 2 .
[0111] 4. Post-baking: Heat bake at 80℃ for 60 seconds to promote cross-linking reaction.
[0112] 5. Development: Use ethyl acetate as the developer, immerse the silicon wafer and clean the unexposed parts.
[0113] 6. Observation: Observe the pattern on the silicon substrate under a microscope and measure the line width resolution.
[0114] Test results:
[0115] Line width resolution: The minimum resolution can reach 5μm.
[0116] Sensitivity: Minimum exposure dose is 25mJ / cm 2 , the pattern is flawless and the contrast is high.
[0117] Elastic modulus: 1.437 GPa.
[0118] Adhesion: The maximum interfacial bonding force between photoresist and silicon wafer is 16.45nN.
[0119] ·Good film forming property, no crystallization, and film roughness is 0.631nm.
[0120] Example 2
[0121] The difference between this embodiment and embodiment 1 is the exposure method: a 254nm light source is used to pattern the embodiment 1, and the patterning result is as follows: Fig.12 shown.
[0122] Example 3
[0123] The difference between this embodiment and embodiment 1 is that the molecular weight of the precursor of the photoresist composition is:
[0124] Tetraene polymer precursor: PEG 1000 NB-MI, wherein n represents the relative molecular weight of polyethylene glycol, specifically 1000 g / mol, accounting for 80 wt % of the total weight.
[0125] Accurately weigh each component: Polyethylene glycol: Mn = 1000 g·mol -1 , 0.2g. The remaining steps and parameters are the same as those in Example 1.
[0126] Test results:
[0127] Line width resolution: The minimum resolution can reach 5μm.
[0128] Sensitivity: Minimum exposure dose is 52mJ / cm 2 .
[0129] Elastic modulus: 1.054 GPa.
[0130] Adhesion: The maximum interfacial bonding force between photoresist and silicon wafer is 16.26nN.
[0131] Good film-forming property, no crystallization, film roughness 0.515nm.
[0132] Example 4
[0133] The difference between this embodiment and embodiment 3 lies in the exposure method: a 254nm light source is used to pattern the embodiment 3, and the patterning result is as follows: Fig.18 shown.
[0134] Example 5
[0135] The difference between this embodiment and embodiment 2 is that the thiol cross-linking agent in the photoresist composition is different:
[0136] ·Mercapto crosslinker: trimethylolpropane tris(mercaptopropionic acid).
[0137] The remaining steps and parameters are the same as those in Example 2.
[0138] Test results:
[0139] ·254nm light source exposure pattern such as Fig.19 shown.
[0140] Adhesion: The maximum interfacial bonding force between photoresist and silicon wafer is 14.99nN.
[0141] Good film-forming property, no crystallization, film roughness 1.75nm.
[0142] Example 6
[0143] The difference between this embodiment and embodiment 5 is that the thiol cross-linking agent in the photoresist composition is different:
[0144] Thiol crosslinking agent: trimethylolpropane tris(thioglycolic acid).
[0145] The remaining steps and parameters are the same as those in Example 5.
[0146] Test results:
[0147] ·254nm light source exposure pattern such as Fig. 22 shown.
[0148] Good film-forming properties, no crystallization, roughness 1.96nm.
[0149] Example 7
[0150] The difference between this embodiment and embodiment 1 is that the organic solvent of the photoresist composition is different:
[0151] Toluene was selected as the organic solvent, and the remaining steps and parameters were the same as those in Example 1. The coating results were as follows: Fig.24 shown.
[0152] Example 8
[0153] The difference between this embodiment and embodiment 1 is that the organic solvent of the photoresist composition is different:
[0154] Dichloromethane was selected as the organic solvent, and the remaining steps and parameters were the same as those in Example 1. The coating result was as follows: Fig.25 shown.
[0155] Example 9
[0156] The difference between this embodiment and embodiment 1 is that the weight percentage of the photoresist composition is different:
[0157] The weight percentage of the precursor: the thiol crosslinking agent: the difuran crosslinking agent is 7:1:2, and the weight percentage of the solvent is propylene glycol methyl ether acetate.
[0158] Test results:
[0159] Elastic modulus: 1.257 GPa.
[0160] Example 10
[0161] The weight percentage of the precursor: the thiol crosslinking agent: the difuran crosslinking agent is 7:2:1, and the weight percentage of the solvent is propylene glycol methyl ether acetate.
[0162] Test results:
[0163] Elastic modulus: 1.028GPa.
[0164] Embodiment 11
[0165] The difference between this embodiment and embodiment 2 is the difference in developer:
[0166] Cyclohexanone was selected as the developer, and the remaining steps and parameters were the same as those in Example 2.
[0167] Example 12
[0168] The difference between this embodiment and embodiment 2 is the difference in developer:
[0169] Isopropyl alcohol was selected as the developer, and the remaining steps and parameters were the same as those in Example 2.
[0170] Example 13
[0171] The photoresist composition film of Example 1 is patterned by electron beam exposure, comprising the following steps:
[0172] Coating: Spin-coat the photoresist composition prepared above on a silicon wafer with a coating thickness of 0.05 μm.
[0173] Pre-bake: Pre-bake at 70°C for 60 seconds to remove the solvent.
[0174] Exposure: Electron beam exposure with an exposure dose of 500μc / cm 2 .
[0175] Post-baking: Heat bake at 80℃ for 60 seconds to promote cross-linking reaction.
[0176] Development: Use ethyl acetate as the developer, immerse the silicon wafer and clean the unexposed parts.
[0177] Observation: Observe the pattern on the silicon substrate with a microscope and measure the line width resolution.
[0178] Test results: Nanoscale resolution of the photoresist composition can be achieved, with a feature size of up to 122nm.
[0179] The above-mentioned embodiment data analysis shows that:
[0180] Comparison of Examples 1, 2 and 3 shows that the molecular weight and the number of thiol groups have a certain influence on the performance of the photolithographic material. 2 The exposure dose of can reach higher line width resolution, showing higher sensitivity. And although the composition in embodiment 2 and 3 can also reach the same line width resolution, the required exposure dose is slightly higher. In addition, in terms of mechanical properties, it can be seen from the elastic modulus and adhesion of comparative examples 4 and 5 that due to the reduction of the ratio of furan crosslinking agent, the pattern mechanical properties formed are poor, which is also the significance of the present invention introducing the third component. In general, the photoresist composition provided by the present invention is applicable to multiple lithography techniques, especially has higher sensitivity for deep ultraviolet light and extreme ultraviolet lithography.
[0181] Examples 7 and 8: Toluene and dichloromethane were selected as solvents, respectively. It was found that these two solvents resulted in poor film-forming properties and solubility, and the presence of insoluble matter and crystallization. This emphasizes the importance of selecting a suitable solvent to ensure the quality of the photoresist solution.
[0182] Example 9 and Example 10: By changing the ratio of precursor, thiol crosslinker and bisfuran crosslinker, the mechanical properties of the photoresist can be adjusted. For example, reducing the ratio of bisfuran crosslinker leads to a significant decrease in elastic modulus from 1.437 GPa to 1.028 GPa, demonstrating the importance of the crosslinker ratio on mechanical properties.
[0183] Example 13: Nanoscale resolution was achieved using electron beam exposure, with a feature size of 122 nm, demonstrating that the material has the potential to achieve high-resolution patterning.
[0184] Comparative Example 1
[0185] Thiol-ene photoresist comparison experiment: compare the performance differences in mechanical strength, pattern rigidity, etc. between the composition of the present invention (pure polymer matrix) and the thiol-ene photoresist without the furan system.
[0186] Experimental materials: A two-component photoresist control group without furan was selected.
[0187] Experimental results: The composition of the present invention exhibits clearer patterns and higher pattern elastic modulus.
[0188] Comparative Example 2
[0189] Metal cluster photoresist comparison experiment: Compare the interface bonding force between the composition of the present invention (pure polymer matrix) and the metal cluster photoresist system.
[0190] Experimental materials: Tin oxide cluster metal photoresist was selected as the control group.
[0191] Experimental results: The metal clusters cannot form a good interface force with the silicon wafer due to insufficient functional groups, so their bonding force is low, 7.83Nn. The composition of the present invention exhibits a higher interface bonding force.
[0192] Comparative Example 3
[0193] Developer comparison experiment. Using water as a developer to develop the photoresist composition
[0194] Experimental materials: Invention Example 1
[0195] Experimental results: The water-developed image has low resolution and contains a large amount of insoluble matter.
[0196] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A photoresist composition, characterized in that Including compounds of formula I, formula II and formula III: In the compound described in formula I: X is selected from one of the olefins; R1 is one of the flexible oligomers; In the compound described in formula II: R2 is selected from one of alkyl, thiol propionate, thiol acetate and aromatic; m is an integer selected from 2 to 8; In the compound described in formula III: R3 is selected from one of alkane, ketone, benzene and ether.
2. The composition according to claim 1, characterized in that: The R1 is selected from one of the following structural formulas: Wherein: n is an integer selected from 1-30.
3. The composition according to claim 1, characterized in that: The R2 is thiol propionate.
4. The composition according to claim 1, characterized in that: The R3 is selected from one of methane, propane, ketone, benzene and thioether.
5. The composition according to claim 1, characterized in that: The weight ratio of the compounds of formula I, formula II and formula III is (5-9): (0.5-2.5): (0.5-2.5).
6. The composition according to claim 5, characterized in that: The weight ratio of the compounds of formula I, formula II and formula III is (6-8): (1-2): (1-2).
7. For the technical solution described above, it is further preferred that the photoresist composition also includes an organic solvent; the organic solvent is selected from at least one of toluene, xylene, n-hexane, dichloromethane, chloroform, ethyl acetate, and PGMEA (propylene glycol methyl ether acetate).
8. A photoresist composition for use in photolithography patterning, characterized in that: Spin coating the photoresist composition according to claim 1 on a silicon wafer or a quartz wafer substrate, and drying to form a photoresist film; The photoresist film is exposed to deep ultraviolet, extreme ultraviolet or electron beam radiation for exposure; low-temperature baking is performed after exposure; and a photolithographic pattern is obtained by developing with a developer.
9. The method for forming a photolithography pattern according to claim 8, characterized in that: The developer is selected from at least one or more of isopropyl alcohol, ethyl acetate, 2-heptanone, 4-methyl-2-pentanone and cyclohexanone.
10. The method for forming a photolithography pattern according to claim 8, characterized in that: The method also includes the steps of baking the silicon wafer with the pattern at a high temperature, transferring the finished product for optical cross-linking to a higher temperature, and finally developing the product with a developer.